A Feministic Analysis of Goodbye Mr. Chips by James Hilton - Huraira, Abu; Anwar, Ali; Khan, Muhammad Talha Shahzad (Pakistan Languages and Humanities Review, 2023)
The present research focuses on the feministic analysis of “Goodbye Mr. Chips” by James Hilton. “Goodbye, Mr. Chips” is a novella that is written in the background of World War-I and raises a feministic point of curiosity. Novel as ever been a source of investigation and scrutiny. The research focuses on analyzing the views of Katherine Bridges and searching out the feminism in Katherine Bridges. Katherine Bridges, in the novel, exposes herself to be a radical feminist. Wollstonecraft (1792) theory of feminism applies to the novel and discusses it regarding feminism. This movement is concerned with women’s rights in society. The woman at that time was considered inferior to man. Feminism is the idea that all genders have equal rights in society. Through this novel writer wants to show the basic and major rights of women that are not given to them, especially the middle and lower class. The selected paragraphs from the novel have been taken as the focus for data discussion in the light of theory. The research proves that the women, even in the pre-world war I, were much advance in thinking and action. Their thoughts were positive and constructive. The research unveils many new vistas for further research.